2022
DOI: 10.1002/solr.202201009
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Annealing Treatment on Hydrothermally Grown Antimony Sulfoselenide Thin Films for Efficient Solar Cells

Abstract: Herein, antimony sulfoselenide (Sb2(S, Se)3) thin‐film solar cells are fabricated by a hydrothermal method followed by a post‐deposition annealing process at different temperatures and the impact of the annealing temperature on the morphological, structural, optoelectronic, and defect properties of the hydrothermally grown Sb2(S, Se)3 films is investigated. It is found that a proper annealing temperature leads to high‐quality Sb2(S, Se)3 films with large crystal grains, high crystallinity, preferred crystal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[39] FTO/CdS/Sb 2 (S,Se) 3 /spiro-OMeTAD/Au 20.44 0.670 62.10 8.48 Exp. [4] FTO/ZnO/CdS/Sb 2 (S,Se) 3 /spiro-OMeTAD/Au 23.70 0.673 66.80 10.70 Exp. [5] ITO/CdS/Sb 2 (S,Se) 3 /Au (HTL free) 26.80 0.515 59.10 8.17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] FTO/CdS/Sb 2 (S,Se) 3 /spiro-OMeTAD/Au 20.44 0.670 62.10 8.48 Exp. [4] FTO/ZnO/CdS/Sb 2 (S,Se) 3 /spiro-OMeTAD/Au 23.70 0.673 66.80 10.70 Exp. [5] ITO/CdS/Sb 2 (S,Se) 3 /Au (HTL free) 26.80 0.515 59.10 8.17…”
Section: Resultsmentioning
confidence: 99%
“…These materials show excellent photoelectric properties, such as tunable bandgap (1.1-1.7 eV), high-absorption coefficient (>10 5 cm À1 ), stability against moisture, as well as low toxicity, environmental friendliness, earth abundance, and finally, simple preparation process. [4][5][6][7][8][9][10] So far, the Sb 2 (S,Se) 3 solar-cell PCE has been quickly enhanced (i.e., over 10%) by material preparation, device configuration, defect passivation, and interface modification. [5,[11][12][13] And these devices are made up of an expensive organic Spiro-OMeTAD hole-transport layer (HTL), demonstrating poor device stability due to the bis(trifluoromethane) sulfonimide lithium salt (Li-TFSI) doping into Spiro-OMeTAD.…”
mentioning
confidence: 99%
“…[ 89,90 ] Rijial et al demonstrated that by applying proper annealing temperatures, high‐quality films with large crystal grains, high crystallinity, preferred crystal orientation, and uniform morphology can be obtained, leading to enhanced carrier transport. [ 91 ] Recently, Che et al investigated the defect evolution during annealing, revealing a two‐step process involving vacancy formation and migration of antimony ions. [ 92 ] This process leads to the generation of cation–anion antisite defects, which have low formation energy.…”
Section: The Strategies For Improving Carrier‐transport Property Of S...mentioning
confidence: 99%
“…Furthermore, Sb 2 X 3 has the advantages of earth-abundance, low eco-toxicity, high absorption coefficient (410 5 cm À1 ), low Urbach energy (B30 meV), low exciton binding energy, readily tunable bandgap (E g B 1.1-1.7 eV, depending on the Se/S ratio), superior physicochemical stability, balanced (ambipolar) charge transport, and ultra-flexibility, satisfying most of the requirements of an ideal PV material. [1][2][3][4][5][6][7] Due to the rapid progress in film deposition strategies and composition and device engineering, PCE values of 8.00%, 8 10.57%, 9 and 10.75% 10 have been reported for Sb 2 S 3 , Sb 2 Se 3 , Department of Physics, Indian Institute of Science, Bengaluru-560012, Karnataka, India. E-mail: kramesh@iisc.ac.in † Electronic supplementary information (ESI) available.…”
Section: Introductionmentioning
confidence: 99%